Progress and prospects in the research on the impact of periodontal disease on systemic diseases and its mechanisms - CHEN Bin, YAN Fuhua (口腔疾病防治)
Periodontal disease is highly prevalent, exerting detrimental effects on oral health and posing serious threats to systemic health. Over the past three decades, research exploring the impact of periodontal disease on systemic diseases has rapidly advanced. Nevertheless, numerous challenges and unanswered questions remain, necessitating further investigation. Therefore, this article first elucidates the association between periodontal disease and systemic diseases. Then, the key evidence supporting their relationship is graded according to the Oxford Centre for Evidence-Based Medicine levels of evidence criteria. Specifically, periodontal disease emerges as an independent risk factor for diabetes mellitus (level A evidence) and cardiovascular diseases (level B evidence). As such, it represents a potential risk factor for rheumatoid arthritis (level B evidence), chronic obstructive pulmonary disease (level B evidence), and inflammatory bowel disease (level B evidence). Furthermore, periodontal disease is closely linked to adverse pregnancy outcomes. Second, this article delineates the plausible mechanisms through which periodontal disease influences systemic diseases, explicitly showing that the foundational elements underlying their connection are bacteria and inflammation. The circulation pathway and saliva pathway specifically mediate this connection. Finally, in light of the current ambiguities surrounding the relationships between periodontal disease and certain systemic diseases, as well as the insufficient depth of mechanism research, this article outlines several considerations for future clinical research and animal experiment designs. Implementing large-sample, multi-center, high-quality clinical studies, utilizing multi-omics analyses for more in-depth exploration of mechanisms, and actively promoting clinical translational research are recommended. This article aims to advance the field of periodontal medicine, while simultaneously offering evidence-based insights to inform the implementation of public health policies.